Carta de Roberto H. Todd a José Tous Soto - Todd, Roberto H.; Tous Soto, José (My University, 1923)
Carta relacionadas a gestiones de Roberto H. Todd en el Congreso.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Thompson, Carmi; Towner, Horace Mann, 1855-1932; Montgomery Reily, Emmet, 1866-1954; Córdova Dávila, Félix, 1878-1938